2013
DOI: 10.1002/adfm.201300589
|View full text |Cite
|
Sign up to set email alerts
|

Dragline, Egg Stalk and Byssus: A Comparison of Outstanding Protein Fibers and Their Potential for Developing New Materials

Abstract: This feature article discusses three remarkable protein fi bers: spider dragline, lacewing egg stalk and mussel byssus. Sequence-structure-function relationships of selected proteins in the fi bers are highlighted and the potential of these proteins for use as new materials is summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 204 publications
(214 reference statements)
0
29
0
2
Order By: Relevance
“…Rather, the HRD peptides formed dense amyloid-like phases under appropriate conditions of concentration and pH without metal ions present (Figure 9). [2,41] Notably, recent X-ray diffraction studies of native distal byssal threads have identified the presence of amyloid-like cross β-sheet structure; [14] however, it is unclear from the present investigation whether HRDs would still form amyloid phases within the thread. [2,41] Notably, recent X-ray diffraction studies of native distal byssal threads have identified the presence of amyloid-like cross β-sheet structure; [14] however, it is unclear from the present investigation whether HRDs would still form amyloid phases within the thread.…”
Section: Role Of Hrds In Precol Assemblymentioning
confidence: 79%
See 2 more Smart Citations
“…Rather, the HRD peptides formed dense amyloid-like phases under appropriate conditions of concentration and pH without metal ions present (Figure 9). [2,41] Notably, recent X-ray diffraction studies of native distal byssal threads have identified the presence of amyloid-like cross β-sheet structure; [14] however, it is unclear from the present investigation whether HRDs would still form amyloid phases within the thread. [2,41] Notably, recent X-ray diffraction studies of native distal byssal threads have identified the presence of amyloid-like cross β-sheet structure; [14] however, it is unclear from the present investigation whether HRDs would still form amyloid phases within the thread.…”
Section: Role Of Hrds In Precol Assemblymentioning
confidence: 79%
“…Protein-based materials formed extracorporeally (i.e., outside the body) similar to the mussel byssus (e.g., insect and spider silks [2] ) face two major challenges for material processing and assembly. Protein-based materials formed extracorporeally (i.e., outside the body) similar to the mussel byssus (e.g., insect and spider silks [2] ) face two major challenges for material processing and assembly.…”
Section: Structure-function Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that proteins with high amounts of glycine, tyrosine and serine formed the epicuticular structures. The composition of the amino acid mixture resembled that of known structural proteins such as fibroin, collagen or resilin [30 -32], which often combine stiffness and toughness [35]. Thus, it can be reasonably assumed that the durability of patterned epicuticle of T. bielanensis to withstand wear in soil habitats results from epicuticular protein structures.…”
Section: Discussionmentioning
confidence: 99%
“…Biological fibers such as spider and cocoon silks are widely used as biological materials in diverse applications (Omenetto and Kaplan, 2010). They have been elucidated in great detail in terms of structure and mechanical properties (Lintz and Scheibel, 2013). However, a complete description of their hierarchical structure and assembly pathway is still underway (van Beek et al, 2002).…”
Section: Introductionmentioning
confidence: 99%